2007
DOI: 10.1093/annonc/mdl379
|View full text |Cite
|
Sign up to set email alerts
|

Poorer outcome of elderly patients treated with extended-field radiotherapy compared with involved-field radiotherapy after chemotherapy for Hodgkin's lymphoma: an analysis from the German Hodgkin Study Group

Abstract: Elderly patients with early-stage unfavorable HL generally have a poorer risk profile and outcome when compared with younger patients. Treatment with EF-RT instead of IF-RT after chemotherapy has a negative impact on survival of elderly patients and should be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Interestingly the outcome in older patients was poorer when they were treated with EF-RT instead of IF-RT (FFTF, 58% vs 70%, P=0.034; OS, 59% vs 81%, P=0.008). Furthermore, increased toxicity was documented when the older patients received EF-RT [40]. In conclusion, EF-RT should be avoided in treating older patients.…”
Section: Early Stagesmentioning
confidence: 92%
“…Interestingly the outcome in older patients was poorer when they were treated with EF-RT instead of IF-RT (FFTF, 58% vs 70%, P=0.034; OS, 59% vs 81%, P=0.008). Furthermore, increased toxicity was documented when the older patients received EF-RT [40]. In conclusion, EF-RT should be avoided in treating older patients.…”
Section: Early Stagesmentioning
confidence: 92%
“…For patients with early stage unfavorable HL, Klimm et al (Klimm, Eich, Haverkamp, et al, 2007) reported in 2007 the GHSC experience for the elderly early stage HL after CMT with 4 cycles of chemotherapy (COPP/ABVD) followed by EF-RT vs. IF-RT. From 1204 patients enrolled in the GHSG HD8 study, 89 patients were 60 years or older.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…The EP recommendations are, therefore, based on the analysis of retrospective studies or on data extracted from sub-groups of elderly patients enrolled into trials originally designed for younger patients. Data extrapolated from the HD8 GHSG study 58 indicate that in patients with early stage disease, without co-morbidities, 2-4 courses of chemotherapy with ABVD followed by limited radiotherapy are well tolerated and produce a high complete remission rate. Extended RT has a negative impact in elderly patients and only limited RT should therefore be adopted as adjuvant to chemotherapy in this category of patients.…”
Section: Treatment Of Elderly Patientsmentioning
confidence: 99%